Factors Affecting Fraud in Management of Village Funds - Jatmiko, Bambang; Pratiwi, Novita Ika; Ardhi, Kholifah Fil (Prosiding International Conference on Sustainable Innovation (ICoSI), 2023)
Introduction – Parties who commit acts of fraud use various modes that can be used to succeed in their actions, such as falsifying records, mark-ups, and documents that are deliberately omitted. Corruption as an act that can harm the wider community or the public/public interest for their own or group interests. Purpose – This study aims to test and prove empirically the impact of the internal control system, apparatus morality, and apparatus competence on fraud in the management of village funds with accountability as an intervening variable. This study used a survey method with a questionnaire tool. Methodology – This research approach uses a quantitative approach with sampling using random sampling technique. Research respondents included village heads, village secretaries, village finance officers, village consultative bodies (BPD) from 59 village governments in Gunung Kidul district. The analysis tool for this study used SPSS version 22.5 for descriptive analysis and SmartPLS v.3 using the Structural Equation Modeling (SEM) analysis method for the analysis of the research model. Findings – The results of this study indicate that the Internal Control System, Apparatus Morality, Apparatus Competence, and Accountability have a negative effect on Fraud in Village Fund Management. The Internal Control System and Apparatus Morality have a negative effect on Fraud in Village Fund Management with Accountability as an intervening variable. Meanwhile, Apparatus Competence has no effect on Fraud in Village Fund Management with Accountability as an intervening variable. Originality/ Value/ Implication - the results of this study can be used as input to address the problem of fraud in the management of village funds.